Relation between high purine intake and hiperurisemia in pre-elderly to late elderly ages - Tiara Diva Maharani; Karima Khoirunisa Ayuningtyas; Aldika Salma Nurhani; Almira Sitasari; Agus Wijanarka; Tri Siswati (Nutrition and Health Insights, 2025)
The prevalence of joint disease in pre-elderly to late elderly ages is quite high (30.3%) and is generally caused by a high purine diet. The purpose of this scoping review is to discuss the relationship between a high purine diet and the incidence of hyperuricemia in the elderly. Methods: Researchers used the scoping review method using academic journals published from 2020 to 2024. The literature was searched using Google Scholar electronic database. Researchers used the following search terms: Asam urat OR Hiperurisemia AND lansia OR elderly AND makanan tinggi purin OR high purine intake AND observasional OR observasional crossectional case control. A total of 93 studies were identified and 9 studies were included in this review. Results: Based on nine journal articles, researchers obtained information regarding the relationship between high purine diet and the incidence of hyperuricemia in the elderly showing varied results in several regions of Indonesia. Most of the journal articles obtained stated that there was an association between a high purine diet and the incidence of hyperuricemia in the elderly. Conclusions: Elderly people who consume foods high in purines can increase uric acid levels in the body so it is necessary to adjust their diet, especially limiting foods that are high in purines.